THE DISCOURSE OF PARLIAMENTARY SPEECHES ON „KOŠARE“ DURING SESSIONS DEDICATED TO KOSOVO AND METOHIJA FROM 1999 TO 2024 - Perišić, Nikola (Political Review, 2025)
During the bombing of the Federal Republic of Yugoslavia and Serbia, simultaneous fighting took place in Kosovo and Metohija against members of the so-called Kosovo Liberation Army (KLA). The bombing, as well as the other conflicts in Kosovo and Metohija, ended with the signing of the Kumanovo Agreement in June 1999. However, this did not resolve the crisis in Kosovo and Metohija, which deepened further with the March Pogrom in 2004 and the unilateral declaration of Kosovo's independence in 2008, furthermore, in recent years it has taken a new form. Despite the signing of numerous agreements over the past decade or so, the position of the Serbian population in Kosovo and Metohija has not improved. As a result, negotiations between Belgrade and Priština were initiated with the mediation of various international organizations and institutions, primarily the European Union, which has been leading the dialogue since 2011. All of this has contributed to the topic of Kosovo and Metohija becoming one of the most dominant for the political elites in Serbia. This is especially evident in the functioning of parliamentary life, as a total of nine extraordinary sessions were convened from 1999 to 2024, aimed at adopting negotiation plans and/or presenting reports from negotiating teams representing Serbia's national interests in those rounds of dialogue. These sessions were often attended by the highest state officials, such as the President of the Republic or the Prime Minister. The sessions typically lasted one day, although in some cases, especially from 2019 onwards, they were extended to two days. This paper will present the extent to which various parliamentary representatives, as well as top state officials, addressed the topic of "Košare" over the past 25 years, and the types of argumentative styles and discourse they employed in doing so.
Keywords: Kosovo and Metohija; Košare; discourse; parliamentary speeches; Kumanovo Agreement